Effect of Drying Methods and Harvest Age on the Quality of Sliced Tiwai Onion (Eleutherine americana Merr) as A Potential Functional Food - Rachmawati, Maulida; Murdianto, Wiwit; Suprapto, Hadi; Apriadi, Rimbawan; Ramadhani, Novandi Eka; Apriliato, Dwi Krisno; Istianah, Lailatus; Badhawi, Muhammad Khafi; Saragih, Bernatal (Trends in Sciences, 2024)
Tiwai onion (Eleutherine americana L. Merr) is renowned for therapeutic properties due to the bioactive constituents, including polyphenol, flavonoid, and tannin. Therefore, this study aimed to characterize water content, ash, fat, protein, polyphenol, flavonoid, tannin, and antioxidant capacity, as well as to observe the functional groups and morphology of dried tiwai powder. The methodology comprised 2 factors, namely harvest age and drying methods. The results showed significant effects of harvest age and drying methods on water, fat, total phenol, total flavonoid, anthocyanin content, and antioxidant capacity, while ash, protein, and tannin content were not significantly affected. In Fourier Transform Infrared Spectroscopy (FTIR) analysis, changes in functional groups were observed, although not significant in wave numbers range of 1,800 - 1,350 and 1,200 - 950 cm−1. Specifically, an increase was observed in signals from C-C, C-O, and C-O-C vibrations. Scanning Electron Microscopy (SEM) at 1000x magnification showed that air drying at 5 months of harvest age produced dense granules, while electric oven and microwave drying of older harvests led to a flatter structure and crumbly texture. HIGHLIGHTS Tiwai Onion’s Medicinal Properties: Tiwai onion (Eleutherine americana Merr) is traditionally used in Indonesia for its medicinal properties, including high levels of polyphenols, flavonoids, and tannins, which contribute to its antioxidant potential, protecting cells from free radicals and supporting overall health. Impact of Drying Methods: The study compares three drying methods-air, electric oven, and microwave-on the water content and bioactive compounds in tiwai. Microwave drying is shown to preserve bioactive compounds like phenols and flavonoids better, while air drying is more suited for heat-sensitive products. Chemical Content Variability: The drying method and harvest age significantly affect the chemical composition of tiwai, including water, fat, protein, and phenolic content. Microwave drying at 5 and 7 months resulted in the highest total phenol content, while air drying retained the most flavonoids at 9 months. Antioxidant Capacity: Despite the different drying methods, no significant variation was observed in the antioxidant capacity of tiwai at different harvest ages. However, microwave drying shows promising results in preserving the active compounds and antioxidant properties. Microstructural Effects: Scanning Electron Microscopy (SEM) revealed that air drying leads to denser, irregular granules with lower solubility, while microwave drying creates more brittle, compact structures, improving solubility and rehydration capacity. GRAPHICAL ABSTRACT